PENGEMBANGAN MEDIA INTERAKTIF BERBASIS CANVA DENGAN MATERI EKOLOGI DAN PELESTARIAN LINGKUNGAN - Kolengsusu, Haris (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
The aim of the research is to determine the development of interactive media based on the Canva application and determine the validity, practicality and effectiveness of interactive media based on the Canva application with ecological and environmental conservation material. The method used in this research is R&D (Research and Development) with the development of Borg and Gall (2014) and uses the steps of knowledge study, development and results. The development of Canva media in scientific disciplines goes through various stages and revisions, namely the validation stage by experts. media and materials with good scores, namely 100% and 78.12%. With an assessment score from media experts, a score of 89% was obtained. And the results of the educator assessment found an average percentage of 84.42% in the "Decent" category. Thus, the Canva media that was designed was stated to be worthy of being tested in the field. And the level of practicality of Canva media products is assessed based on questionnaires filled out by students in response questionnaires resulting in an average percentage of 84.55% so that they fall within the practicality criteria of "very interested"